Multidrug-Resistant Tuberculosis in Alberta and British Columbia, 1989 to 1998 - Ahmed Hersi; Kevin Elwood; Robert Cowie; Dennis Kunimoto; Richard Long (Canadian Respiratory Journal)
OBJECTIVE: To describe the extent of the problem of multidrug-resistant tuberculosis (MDR-TB) in Alberta and British Columbia from 1989 to 1998.